Exploring the Impact of University Support and Theory of Planned Behavior on Entrepreneurial Intentions: A Mediated Model Analysis - Veronica Cynthia Wijayanti; Leny Noviani Noviani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Higher education institutions aim to cultivate entrepreneurial aspirations among students. However, challenges persist in effectively fostering new entrepreneurs. This study examines the role of higher education support in influencing students’ entrepreneurial intentions, framed within the Theory of Planned Behavior (TPB). A quantitative survey design was employed, gathering primary data from 256 undergraduate students engaged in the MBKM entrepreneurship program across 10 universities in Surakarta. Data analysis utilized Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software to test the relationships between higher education support, TPB constructs, and entrepreneurial intentions. The findings reveal that higher education support does not directly affect students’ entrepreneurial intentions. However, it significantly impacts these intentions indirectly through TPB variables: attitudes towards entrepreneurship, subjective norms, and self-efficacy. These mediating variables highlight the importance of fostering positive attitudes, supportive social norms, and confidence in entrepreneurial capabilities to enhance students’ entrepreneurial intentions. The results suggest that higher education institutions should focus on strengthening TPB-related factors within entrepreneurship programs to indirectly motivate students toward entrepreneurship. Collaboration between universities, government, and the business sector is essential to enhance the entrepreneurial ecosystem. Entrepreneurship programs must be continuously refined to effectively support students' entrepreneurial journeys. Universities should leverage partnerships to create an integrated support system that aligns with TPB principles, fostering a conducive environment for entrepreneurship development.